2020
DOI: 10.1101/2020.03.09.983841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiota–modulated enteric neuron translational profiling uncovers a CART+ glucoregulatory subset

Abstract: Microbial density and diversity increase towards the distal intestine, affecting tissue physiology, metabolism, and function of both immune and nervous systems. Intrinsic enteric-associated neurons (iEAN) continuously monitor and modulate intestinal functions, including nutrient absorption and motility.Through molecular, anatomic and functional approaches, we characterized the influence of the microbiota on iEAN. We found that iEAN are functionally adapted to the intestinal segment they occupy, with a stronger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…Moreover, microorganisms that produce SCFAs in the gut have been demonstrated to suppress gut motility. These findings support the theory that the microbiome participate in gut motility regulation through gut-to-brain signaling (Kelly et al, 2015;Muller et al, 2020). The understanding of the effect of neuroactive compounds on gut microbiome composition and activity is still limited despite significant efforts.…”
Section: Impact Of Neuroactive Compounds On the Gut Environmentsupporting
confidence: 81%
“…Moreover, microorganisms that produce SCFAs in the gut have been demonstrated to suppress gut motility. These findings support the theory that the microbiome participate in gut motility regulation through gut-to-brain signaling (Kelly et al, 2015;Muller et al, 2020). The understanding of the effect of neuroactive compounds on gut microbiome composition and activity is still limited despite significant efforts.…”
Section: Impact Of Neuroactive Compounds On the Gut Environmentsupporting
confidence: 81%
“…In addition, studies have shown that the NLRP6 inflammasome activates Caspase-11 and induces loss of gut-associated neurons. After the microbiota is depleted, specific intestinal neurons involved in glucose regulation are absent, resulting in elevated blood glucose and IR (86,87). Additionally, activation of the NLRP6 inflammasome-induced the secretion of IL-1b and IL-18 probably involved in the regulation of IR (Figure 6).…”
Section: Nlrp6 Inflammasome and Irmentioning
confidence: 99%
“…The conversation between the gut and organs is carried out through a complex microbial-neuro-endocrine network, cocaine-and amphetamine-regulated transcript (CART + ) neurons regulated by microorganisms can directly interact with pancreas and liver through sympathetic nerves, affecting insulin secretion and liver gluconeogenesis and glycogenolysis (Muller et al, 2020). Bile acid is an important messenger constituting enterohepatic dialog, and are synthesized in the liver and participate in the digestion of food.…”
Section: The Influence Of Microbiota-gut-liver Axis On Blood Glucosementioning
confidence: 99%